PERAN GURU PAI DALAM MENANGKAL RADIKALISME DI SEKOLAH (Best Practice di SMK Khoiriyah Hasyim Tebureng Jombang) - Farhan, Agung Zulfiqar; Said, Ali (Universitas Pendidikan Indonesia, 2021)
Abstract. The phenomena of radicalism that use Islamic attributes, both in Indonesia and in the world, are very worrying. Islamic religious education in schools is required to be able to counteract the seeds of radicalism infecting the younger generation of the nation’s successors. The role of Islamic Religious Education (Pendidikan Agama Islam-PAI) teachers in this regard is also very much needed. This study wanted to know the role of PAI teachers at Sekolah Menengah Kejuruan (Vocational School) Khoiriyah Hasyim in countering radicalism. This research uses desciptive qualitative approach. The results of this study indicate that PAI teachers at this school play a very important role in anticipating radicalism. Based on the 5 basic principles of Pesantren Tebuireng, namely sincerity, honesty, hard work, tolerance, and responsibility, PAI teachers at Khoiriah Hasyim Vocational School have made efforts so that students at the school are not trapped in radical ideas. Keywords: The role of PAI teachers, Radicalism in schools, PAI in schools. Abstrak. Fenomena radikalisme yang menggunakan atribut-atribut Islam, baik di Indonesia maupun di dunia, sangatlah mengkhawatirkan. Pendidikan Agama Islam di Sekolah dituntut untuk bisa menangkal benih-benih radikalisme tersebut menjangkiti generasi muda penerus bangsa. Peran guru Pendidikan Agama Islam (PAI) dalam hal ini juga sangat dibutuhkan. Penelitian ini ingin mengetahui peran guru PAI di SMK Khoiriyah Hasyim dalam menangkal radikalisme. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Hasil dari penelitian ini menunjukkan bahwa guru PAI di sekolah ini sangat berperan dalam mengantisipasi paham radikalisme. Dengan berlandaskan pada 5 prinsip dasar Pesantren Tebuireng, yaitu Ikhlas, jujur, bekerja keras, toleransi, dan tanggung jawab, guru PAI di SMK Khoiriah Hasyim telah berupaya agar siswa di sekolah tersebut tidak terjebak pada paham-paham radikal. Kata Kunci: Peran Guru PAI, Radikalisme di sekolah, PAI di sekolah.